Use of GeoGebra integrated Screencast Media: Can it help students improve mathematical understanding in Online Tutorial Activities? - Novianti, Idha (International Journal of Mathematics and Sciences Education, 2024)
The Calculus I course is a course that has a high level of difficulty, it is important for tutors to find the right way to convey mathematical concepts in this course. One method used to help students understand the Calculus 1 course is by using Screencast Media assisted by the Geogebra application. This research aims to determine the effectiveness of using Screencast media assisted by Geogebra in improving mathematical understanding skills in the Calculus I course. This research design uses One Group Pretest-Posttest Design. The participants involved in this research were 35 online tutorial students who took the Calculus I course. Furthermore, data collection in this research used a concept understanding test. Data obtained from the test results were analyzed using the one sample t-test. The research results show that the use of screencast media assisted by Geogebra effectively increases students' mathematical understanding in the calculus I course. Students can easily understand mathematical concepts conveyed through video screencasts assisted by Geogebra. Thus, the implementation of this media is expected to improve the quality of teaching and mathematical understanding of students in higher education.